Socio - Economic Impact of Remittance on Households in Lekhnath Municipality, Kaski, Nepal - Dhungana, Ananta Raj; Pandit, Dipendra (Economic Literature, 2016)
The study aims to explore the impact of remittance on social and economic status at households. For this purpose, one hundred and forty seven households having migrant family member (at least one) were selected in Lekhnath Municipality of Kaski District, Nepal. The information was collected via interview by using structured interview schedule. Descriptive as well as inferential statistics were carried out to analyze the impact of remittance. Paired t-test was carried out to see the economic change before and after the remittance received. The impact of remittances on both economic status and the social status of the sampled households is remarkable. The perceived status of the household in the past migration period is better than that in the pre-migration period. Yearly remittance in a household is significantly associated with other socio-economic variables. So, overseas remittance has brought a qualitative change in children’s education and health status. An improvement in the economic status of migrant households, the involvement of the household in community development activities, and participation of the household in social organization have brought a positive change in the overall socio-economic status of the migrant households.Economic Literature Vol.12 2014: 39-49